Hematological parameters during concurrent chemoradiotherapy as potential prognosticators in patients with stage IIB cervical cancer - Oyeon Cho; O Kyu Noh; Young-Taek Oh; Suk-Joon Chang; Hee-Sug Ryu; Eun Ju Lee; Mison Chun (Tumor Biology)
We hypothesized that hemoglobin levels, absolute neutrophil count, and absolute lymphocyte count were associated with radiotherapy response and cancer progression and that they might reflect tumor repopulation during concurrent chemoradiotherapy. This study aimed to investigate these hematological parameters as prognosticators of cervical cancer. We analyzed 105 stage IIB cervical cancer patients treated with concurrent chemoradiotherapy, using log-rank tests and multivariate analyses. Hazard ratios were calculated weekly to evaluate changes in hemoglobin, absolute neutrophil count, and absolute lymphocyte count that were associated with disease-specific survival. Patients were categorized into the high hematological risk (patients with low hemoglobin plus high absolute neutrophil count and/or low absolute lymphocyte count) and the low hematological risk (others) groups according to the median cutoff values. During the second week of concurrent chemoradiotherapy, hematological factors were significantly associated with survival. In multivariate analysis, hematological risk was independently associated with disease-specific survival and progression-free survival. The 5-year disease-specific survival and progression-free survival rates in the high hematological risk group were significantly lower compared with those in the low hematological risk group (81.6% vs 92.6%, p  = 0.0297; 73.7% vs 89.3%, p  = 0.0163, respectively). During the second week of concurrent chemoradiotherapy, the hematological parameters could predict treatment outcome in stage IIB cervical cancer.